The Impact of Profitability, Capital Intensity, and Firm Size on Tax Avoidance: Evidence from Indonesia’s Food and Beverage Sector (2020–2022) - Haryanto, Lenawati; Ramadhanty, Fazrina (Majalah Ilmiah Bijak, 2025)
Differences in interests between taxpayers and the government give rise to tax avoidance by taxpayers, one of which is by exploiting loopholes in tax law. In Indonesia, the issue of tax avoidance is also of concern to the government and tax authorities, therefore this research is to provide an understanding of the factors that influence tax avoidance. This research aims to determine and analyze the influence of profitability, capital intensity and company size on tax avoidance. It is hoped that the results of this research can provide policy input that is relevant to the Indonesian tax context. The sample in this research is food and beverage sub-sector companies for the 2020–2022 period. The sample selection technique used the purposive sampling method to obtain a sample of 18 companies with 54 observation data. After outliers there were 49 data used as samples in this research. This test uses SPSS 25 software and data analysis uses multiple linear regression analysis. Suggestions for further research include adding other variables and expanding the research period. The results of this research show that profitability has a positive effect on tax avoidance, capital intensity has a positive effect on tax avoidance, and company size has a positive effect on tax avoidance.